The use of neutrophil-to-lymphocyte ratio (NLR) as a marker for COVID-19 infection in Saudi Arabia: A case-control retrospective multicenter study - Sayed, Anwar A.; Allam, Assem A.; Sayed, Ayman I.; Alraey, Mohammed A.; Joseph, Mercy V. (Saudi medical journal, 2021)
To assess the neutrophil-to-lymphocyte ratio (NLR) diagnostic and prognostic value in the context of Coronavirus disease-2019 (COVID-19) infection in Saudi Arabia. A case-control study in which 701 confirmed COVID-19 patients (of which 41 were intensive care unit [ICU]-admitted) and 250 control subjects were enrolled. The study was conducted retrospectively in October on patients admitted to 3 separate hospitals in Saudi Arabia namely: King Abdullah Bin Abdulaziz University Hospital (Riyadh), Ohud Hospital (Madinah), and Nojood Medical Center (Madinah) between May and September 2020. Neutrophil-to-lymphocyte ratio was calculated based on absolute neutrophil and lymphocyte count. Institutional ethical approval was obtained prior to the study. Patients (median age 35 years), of which 54.8% were females, were younger than the control cohort (median age 48 years). Patients had significantly higher NLR compared to the control group. Intensive care unit admitted patients had significantly higher platelet, WBC and neutrophil counts. The ICU patients' NLR was almost twice as of the non-intensive patients. The NLR value of 5.5 was found to be of high specificity (96.4%) and positive predictive value (91.4%) in diagnosing COVID-19. Furthermore, it had a very good sensitivity (86.4%) in predicting severe forms of disease, such as, ICU admission. Neutrophil-to-lymphocyte ratio is an important tool in determining the COVID-19 clinical status. This study further confirms the prognostic value of NLR in detecting severe infection, and those patients with high NLR should be closely monitored and managed.